Effects of physical activity on clinical and inflammatory markers in diagnosing multiple myeloma patients - Wang, Jiaping; Sheng, Lixia; Lai, Yanli; Ouyang, Guifang; Xu, Zhijuan (Frontiers in Physiology, 2023)
Multiple Myeloma (MM) is the second most hematological disorder. Although several drugs have been developed to treat MM, their efficacy is uncertain. Also, how normal physical activities impacted the MM patients in decreasing inflammatory response and clinical biomarkers needs to be better defined. Therefore, this study evaluated the possible clinical and inflammatory markers to determine the early diagnosis of MM during physical activity. This study selected 20 MM patients with normal and no physical activity with an age of > 50yrs. This study did not follow any specific exercise protocols rather than noting patients' day-to-life activities and considered them as physical activity. After 30 days of evaluation of their physical activities, the blood sample was collected to assess clinical and inflammatory markers. Regarding clinical markers, moderate physical activity in MM patients increased the LDH level and calcium level compared to other clinical biomarkers such as creatine, total protein, and beta 2 microglobulins. Further, this study observed no significant differences between the physical activity of MM patients and normal MM patients regarding the antibodies level such as IgA, IgD, free kappa, and lambda chain levels except IgM level. However, the IL-6 level was significantly increased with the MM with physical activity compared to MM patients. In conclusion, normal day-to-life physical activity impacted increasing anti-inflammatory response and IgM along with increasing LDH and total calcium levels in MM patients.